Comparison between the counter immunoelectrophoresis test and mouse neutralization test for the detection of antibodies against rabies virus in dog sera - Silva, Luzia Helena Queiroz da [UNESP]; Bissoto, César Eduardo [UNESP]; Carvalho, Cristiano de [UNESP]; Cardoso, Tereza Cristina [UNESP]; Pinheiro, Devani M [UNESP]; Perri, Silvia Helena Venturoli [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 2002)
The detection of rabies antibodies is extremely valuable for epidemiological studies, determination of immune status in man, animals, and for the diagnosis of the disease. Several serological procedures have been described for this purpose. The present study reports a comparison between counterimmunoelectrophoresis test (CIET) and mouse neutralization test (MNT) in the detection of antibodies against rabies virus from 212 serum samples of vaccinated dogs. The agreement between both techniques was 79.7% and a significative association was demonstrated. The correlation coefficients between MNT and the CIET titers was determined considering 88 samples showing positive results in both techniques [CIET = 2 and MNT = 5 (0.13 IU/ml)] and resulted r² = 0.7926 (p < 0.001). The performance of CIET system was technically simple, cheap and rapid, and thereby it could be useful for serological monitoring of dog vaccination campaigns as well as for individual analysis.
Keywords: rabies; rabies antibodies; mouse neutralization test; counterimmunoelectrophoresis test